Occupational disparities in tumor grade and cytosolic HMGB1 expression in renal cell cancer. Issue 1 (16th June 2022) - Zaitsu, Masayoshi; Takeuchi, Takumi; Zaitsu, Masaaki; Tonooka, Akiko; Uekusa, Toshimasa; Miyake, Yudai; Kobayashi, Yasuki; Kobashi, Gen; Kawachi, Ichiro
Abstract: Objectives: We sought to examine occupational disparities in tumor grade and cytosolic expression of high‐mobility group box‐1 (HMGB1) among renal cell cancer (RCC) patients. Methods: This retrospective study included 318 RCC patients with complete information on occupation and pathology in Kanagawa Cancer Registry (KCR). Longest‐held occupations were grouped into manual workers (e.g., manufacturing, construction) versus "others." Odds ratios (OR) and 95% confidence intervals (CI) for high‐grade histology were estimated by logistic regression, adjusted for age and sex. We also examined a sub‐sample of 74 low‐grade RCC inpatients to estimate the OR for positive cytosolic HMGB1 expression in manual workers, adjusting for age, sex, and other available covariates. Results: High‐grade tumors were more prevalent in manual workers compared to other occupations: 23.0% (14/61) versus 10.9% (28/257, p  = .01) with an adjusted OR of 2.28 (95% CI, 1.11–4.69). In the sub‐sample of low‐grade RCCs, positive cytosolic HMGB1 expression was more prevalent in manual workers compared to other occupations: 71.4% (10/14) versus 38.3% (23/60, p  = .03) with a sex‐ and age‐adjusted OR of 3.76 (95% CI, 1.03–13.7). Conclusions: Manual workers are associated with increased risks of high‐grade renal cell tumors and cytosolic HMGB1 expression.